Health belief model for empowering parental toothbrushing and sugar intake control in reducing early childhood caries among young children—study protocol for a cluster randomized controlled trial - Ketian Wang; Gillian Hiu Man Lee; Pei Liu; Xiaoli Gao; Samuel Yeung Shan Wong; May Chun Mei Wong (Trials, 2022)
Abstract Background It has been recognized that oral health education for parents is critical for preventing early childhood caries (ECC). Few parents practiced caries prevention procedures for their children in daily life, though. A novel intervention scheme using mobile messages will be developed in this study under the framework of the health belief model (HBM). The objective of the present randomized clinical trial (RCT) is to evaluate the effectiveness of the new scheme in promoting oral health of young children by reducing dental caries. Methods This RCT will involve 26–36 child care centers or kindergartens with nursery classes (clusters) located in Hong Kong. A total of 518–628 child-parent dyads (child age 18–30 months) will be recruited and randomly allocated at the cluster level into the test or control group with a 1:1 ratio. For parents in the test group, the intervention will consist of a set of HBM-based text messages sent regularly in 48 weeks. A standard text message will be sent to the parents in the control group in the first week. The primary outcome will be dental caries measured by dmft/dmfs of the children after 2 years (around 4 years of age). The secondary outcomes will be toothbtushing and sugar intake. Discussion HBM-based intervention via a low-cost text messaging vehicle may serve as a viable way to empower parents to establish proper oral health behaviors for their children and safeguard the oral health of children in Hong Kong. Trial registration ClinicalTrials.gov NCT04665219 . Registered on 11 December 2020.